THE EFFECT OF SLIMMING HERBS TEA WITH DIETARY ADJUSTMENT TO THE RESULT OF ANTROPOMETRIC MEASUREMENT AMONG WOMEN MEMBER OF AEROBIC STUDIO - Perslami, Resti; Puruhito, Edith Frederika; Agil, Mangestuti (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Overweight is the accumulation of excessive fat that can harm health. People who are overweight usually have a size of body anthropometry more than normal, such as the size of the waist circumference (WC), upper arm circumference (UAC), and subcutaneous fat thickness (SFT). Women are more to being overweight, because metabolism in women is lower and body fat is more than men. They attempt to return to normal body weight, by following the fitness clubs, diet and so forth. In this study, researchers used a slimming herbs tea to help restore their body size. Purpose: This study was to determine the effects of slimming herbs tea with dietary adjustments to the results of anthropometric measurements in the group of gymnastic class women. Method: The method used is quasy experimental design with the design of